John N. Sherwood: studies of energetic materials - Vrcelj, Ranko; Gallagher, Hugh G.; Halfpenny, Peter J. (American Chemical Society (ACS), 2023)
The studies on the physico-mechanical properties of commonly used energetic materials (EMs) that were pursued by the group led by Professor John Sherwood are reviewed in this paper. The studies ranged from the growth of high quality single crystals and the characterisation of their defect and dislocation structures, mechanical testing, through to the study of polymorphism of EM crystals and fundamental aspects of crystallization processes generally. The work performed lead to the definition of good growth conditions for all the EMs studied and to the full characterization of the defect structure, slip systems and hardness properties of cyclotrimethylene trinitramine (RDX) and pentaerythritol tetranitrate (PETN). Partial characterization of the defect structures and hardness properties of cyclotetramethylene tetranitramine (HMX) and 2-4-6 trinitrotoluene (TNT) were also achieved. Additionally, fundamental crystal growth and polymorph information was defined, allowing a deeper understanding of the crystallization and crystal structure of TNT. In addition to the general review, some thoughts as to possible future routes for further study that could suitably utilize the complementary nature of established and modern techniques.
Keywords: Crystal growth; crystallization; Energetic materials; Explosives